Generation Z Purchasing Behavior Profile in the Digital Economy: Normative Analysis in Online Markets - Zhulal, Muhammad; Marits, Shofi Arofatul; Herman, Sebastian (LPPM Institut Bisnis dan Informatika Kesatuan, 2023)
This research aims to detail Generation Z's purchasing behavior in the online market. This research provides an in-depth view for e-commerce companies and marketers to develop more effective strategies in attracting and retaining Generation Z. This research method is normative descriptive research. The type of research used is exploratory research. Data collection techniques involve literature reviews from various journal sources and related literature. The data analyzed is secondary data and the data analysis method involves normative analysis to identify the differences between